Navigating Face-To-Face Communication in the Era of Remote Work among Gen Z - Maharani, Risma; Purwaningwulan, Melly Maulin; Solihat, Manap (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Generation Z faces difficulties in communicating due to remote working, although they are tech savvy, their ability to interact face-to-face and their levels of “digital fatigue” have declined. The aim of this research is to investigate how generation z communicates with one another in the era of remote working, and also to develop an integrative communication model to help bridge human connections in the workplace. This transition has create an ambivalent professional landscape for them. As digital natives, they possess technological navigation skills that surpass those of previous generations. For gen z informants experienced in hybrid work, we employed a qualitative exploratory approach using purposive sampling techniques. The Braun & Clarke method was used to analyse the data. Finding indicate that face-to-face communication remains crucial for picking up non-verbal cues (such as eye contact and belonging). Nevertheless, there is a sense of “professional social anxiety” when interacting spontaneously without digital filters. Conclusion gen z values digital flexibility but requires direct connections for mentoring and career progression. Helping gen z realise that the anxiety they experience when interacting without a “digital filter” is a collective phenomenon that must be addressed if they are to advance in their careers. Implications & recommendations the research supports social presence theory. It is strongly recommended that organisations implement a structured “Team Communication Agreement”. Recommendations to avoid staff turnover and intergenerational collaboration issues, companies must create a psychologically safe environment to develop the soft skill of younger employees.